2005
DOI: 10.1007/s11096-004-3705-y
|View full text |Cite
|
Sign up to set email alerts
|

Medication errors when transferring elderly patients between primary health care and hospital care

Abstract: Medication errors are common when elderly patients are transferred between primary and secondary care. Improvement in documentation and transferring data about elderly patients' medications could reduce these errors. The specific medication dispensing system that has been used in order to increase safety in medication dispensing does not seem to be a good instrument to reduce the number of errors in transferring data about medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
79
3
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 21 publications
8
79
3
2
Order By: Relevance
“…Limitations in the process, as described below, and also too low a power to detect a significant difference might be the explanation. We have previously developed and shown that the medication report in a discharge summary decreases medication errors, clinical consequences, and health contacts due to errors occurring when patients are discharged from hospital to community health care [18,19]. This study shows a further decrease in error rates by improving the internal hospital discharge process.…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…Limitations in the process, as described below, and also too low a power to detect a significant difference might be the explanation. We have previously developed and shown that the medication report in a discharge summary decreases medication errors, clinical consequences, and health contacts due to errors occurring when patients are discharged from hospital to community health care [18,19]. This study shows a further decrease in error rates by improving the internal hospital discharge process.…”
mentioning
confidence: 77%
“…We have previously developed and shown that the medication report in a discharge summary decreases medication errors, clinical consequences, and health contacts due to errors occurring when patients are discharged from hospital to community health care [18,19]. This study shows a further decrease in error rates by improving the internal hospital discharge process.In 2000-2001, we performed a descriptive but otherwise identical study in the same setting to describe the medication error rates [18]. The proportion of medications with medication errors after discharge and return to primary care was 17% and only 46% of the patients had no error at all.…”
mentioning
confidence: 77%
See 3 more Smart Citations